THU0398 Beneficial Effects of in Vivo Ubiquinol Supplementation on Athero-Thrombosis Prevention in Antiphospholipid Syndrome Patients. Preliminary Results of a Clinical Trial. (9th June 2015) - Lopez-Pedrera, C.; Perez-Sanchez, C.; Aguirre, M.; Velasco, F.; Ruiz-Limon, P.; Barbarroja, N.; Jimenez-Gomez, Y.; Segui, P.; Collantes-Estevez, E.; Fernandez del Rio, L.; Vilalba, J.; Gonzalez-Reyes, J.; et al.
Abstract : Background: Previous studies highlighted the beneficial effects of CoQ10 supplementation in clinical conditions such as cardiovascular disease. Objectives: To investigate the beneficial effects of in vivo ubiquinol (Q, reduced form of CoQ10) supplementation on athero-thrombosis prevention in APS patients. Methods: The study was conducted on 20 APS patients randomized to receive either Q (200 mg/day) or placebo for one month. Blood was drawn at time 0 and at the end of the treatment. Studies were performed in plasma and purified leukocytes subsets. Plasma Q levels, various prothrombotic/proinflammatory parameters, and oxidative stress biomarkers were evaluated. Endothelial activity analysis was performed by Laser-Doppler measurement of post ischemic reactive hyperemia. Carotid intimae media thickness (CIMT) was measured as an early atherosclerosis marker. Results: Seventeen out of 20 patients completed the intervention, which increased significantly plasma Q levels. Endothelial function improved notably, as shown by the amelioration in the highest perfusion value after occlusion was released, expressed as a percentage of change vs rest flow value (RF-PF). CD14highCD16- classical monocyte count was not changed, but CD14highCD16+ intermediate monocytes and CD14dimCD16+ non-classical monocytes were decreased. Q treatment decreased Tissue Factor (TF) expression levels in total monocytes, and more notably in intermediate monocytes, which also displayed a more robust reduction of intracellular IKK levels. Only this monocyte subset exhibited IL-8 reduction after intervention. Q supplementation produced a reduction in both the levels of peroxides and the percentage of monocytes with altered mitochondrial membrane potential (ΔΨm). Correlation studies showed that reduced monocyte TF expression after Q treatment were related to decreased peroxides levels, increased plasma Q levels and improved endothelial function. Improved endothelial function further correlated with IL8 levels. The decrease of non-classical monocytes count was related to reduction in the percentage of cells with altered ΔΨm as well as with the increase in RF-PF value. Q effects were particularly relevant in APS patients suffering from arterial thrombosis (AT) or showing pathologic CIMT since TF, IKK and peroxide levels, being particularly higher at baseline in that patients in comparison to those with venous thrombosis (VT) or obstetrical manifestations (OM), showed a more pronounced decline and endothelial function was better improved. Conversely, IL-8 levels, higher at baseline in patients suffering VT or OM, were found reduced after Q administration in those patients. Conclusions: Q supplementation at 200 mg/d significantly improved endothelial function, and reduced mitochondrial dysfunction, oxidative stress, and the expression of prothrombotic/ proinflammatory proteins. Our results support the potential impact of Q in the prevention of atherothrombosis in APS patients. Acknowledgements: Supported by: CTS-7940, PI12/01511, Spanish Rheumatology Society, KANEKA. Disclosure of Interest: None declared